Hydrometeorology, Sediment Dynamics, and Peak Flow Analysis of the Manohara Watershed, Kathmandu, Nepal - Pokhrel, Prativa; Pandey, Sanjeeb; Paudyal , Kabi Raj; Pathak, Dinesh (Journal of Nepal Hydrogeological Association, 2025)
The Manohara River, a fifth order river, is located in the north-east part of the Kathmandu Valley. Manohara River is the main source of groundwater for Madhyapur Thimi, Changunarayan, Sali Nadi, Tribhuvan International Airport and other places located around this river. The research work mainly focusses on the Hydrometrological impacts, sediments distribution and peak flow estimation of the Manohara River covering the area of the Kathmandu and Bhaktapur districts within its watershed. Desk and field study were carried out to collect primary and secondary data: and was used to interpret the sediment distribution and the peak flow of different return period of the Manohara Watershed. Data from Department of Hydrology and Meteorology were collected to study the variation in the rainfall pattern within the study area. The Manohara watershed experiences highest rainfall during the monsoon season, with less precipitation in post-monsoon. Rainfall is highest in the northeast while decreases along the southwest, influencing sediment transport from boulders upstream to finer materials downstream. The Manohara Watershed experienced significant variations in annual average precipitation, with a maximum of 7.4 mm in 2016 in the Sankhu section and a minimum of 1.97 mm in 1991 in the Airport section, while the Bhaktapur section recorded a yearly maximum of 195 mm in 2002. Estimating peak flow rates using the updated DHM method yielded maximum discharges of 455 m³/s and 92 m³/s for 100-year and 2-year return periods, respectively, while the Dickens method provided estimates of 325 m³/s and 110 m³/s for the same periods.